Desvio tangencial de obstáculos para um robô móvel navegando em ambientes semi-estruturados - Ferreira, André (2004)
This thesis proposes a new strategy for a mobile robot to deviate from obstacles while navigating in a semi-structured environment. The proposed control architecture is based on a reactive approach, thus demanding low computational e®ort. It allows the robot to navigate from a starting point to a destination point without colliding to any obstacle in its path. The deviation from an obstacle is performed according to an escape angle calculated so that the new robot orientation is tangent to the obstacle. It is also shown that such strategy generates more e±cient trajectories, in the sense that the destination point is reached in less time while saving energy and reducing the demand on the robot motors. Another interesting aspect of the proposed strategy is that it also allows to implement the behaviors Wall Following and Corridor Following. The proposed methodology is validated through simulated examples and practical experiments as well, which were run in a PIONEER 2-DX mobile robot.